Prostatic fluid composition and semen quality in dogs with benign prostatic hyperplasia undergoing treatment with osaterone acetate. Issue 1 (2nd November 2021) - Ferré‐Dolcet, Lluis; Frigotto, Lisa; Contiero, Barbara; Bedin, Silvia; Romagnoli, Stefano
Abstract: Benign prostatic hyperplasia (BPH) may alter prostatic fluid biochemical composition causing reduced fertility. Osaterone acetate (OA) is an androgen receptor antagonist marketed for treatment of canine BPH. Little information exists on effects of OA administration on biochemical composition of canine prostatic fluid and its role on fertility. The aim of this research was to study biochemical composition of prostatic fluid and its role on semen quality in dogs with BPH undergoing treatment with OA. Eight intact, 5–11‐year‐old dogs with benign prostatic hyperplasia were treated orally with OA at a dose of 0.25–0.5 mg/kg once daily for seven days. Prostatic volume, semen evaluation and a biochemical analysis of prostatic fluid were performed on the day before treatment (D0), D60, D120, D180 and D240. A significant reduction (57% and 61%) of prostatic volume was observed at D60 and D120, respectively, and a significant reduction (20%) of normal spermatozoa was observed at D60 coincident with a significant increase of sperm tail defects, which disappeared during the course of the treatment. Prostatic fluid composition did not vary during the OA treatment except for zinc (Zn 2+ ) with a significant increase at D120 and D180 correlated with the return to normal sperm values. In conclusion, canine Zn 2+ prostatic fluid concentrations decrease during development of BPH and return to normal during treatment with OA. Zn 2+ is an important electrolyte for semen quality, suggesting that oral Zn 2+ supplementation might be considered a treatment to improve semen quality.